Fly in to work; fly out to Bali: An exploration of Australian fly-in-fly-out (FIFO) workers leisure travel. (March 2016) - Sanders, Dale; Willson, Greg; Susomrith, Pattanee; Dowling, Ross
Abstract: The Fly-in-fly-out (FIFO) phenomenon is of significant importance to Australia's economy. A growing body of literature has focused primarily on the relationships between FIFO work and the well-being of workers and their family, and the economic and social impacts of FIFO work on host and source communities. However, there is a lack of scholarly attention paid towards the leisure and travel motivations and behaviours of these workers. The purpose of this exploratory research is to provide a deeper understanding of the travel behaviour of Australia's FIFO workers to one of the country's most popular outbound tourism destinations, Bali in Indonesia. A qualitative approach of in-depth interviews with FIFO workers and family members was used to meet the research aim. This paper is of significance to the Australian tourism industry as it provides some understanding of the factors contributing to the growing disparity between the growth of outbound travel and reduced domestic intrastate and interstate travel. It contributes to academic knowledge through providing greater insight into the complexities involved with FIFO workers' travel motivation and behaviour.